Long-run economic, budgetary and fiscal effects of Roma integration policies - Pavel Ciaian; Adrey Ivanov; D'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2018)
Although, the need for an efficient Roma integration policy is growing in Europe, surprisingly little robust scientific evidence regarding potential policy costs and expected benefits of alternative policy options has supported the policy design and implementation so far. The present study attempts to narrow this evidence gap and aims to shed light on long-run economic, budgetary and fiscal effects of selected education and employment policies for the inclusion of the marginalised Roma in the EU. We employ a general equilibrium approach that allows us to assess not only the direct impact of alternative Roma integration policies but also to capture all induced feedback effects. Our simulation results suggest that, although Roma integration policies would be costly for the public budget, in the medium- to long-run, economic, budgetary and fiscal benefits may significantly outweigh short- to medium-run Roma integration costs. Depending on the integration policy scenario and the analysed country, the full repayment of the integration policy investment (positive net present value) may be achieved after 7 to 9 years. In terms of the GDP, employment and earnings, the universal basic income scenario may have the highest potential, particularly in the medium- to long-run.
Keywords: J6; J11; J24; O17; O43; I32; 330; Roma; social marginalisation; education; labour market; integration policy; universal basic income